Highly impaired platelet ultrastructure in two families with novel IKZF5 variants. (19th May 2021) - Leinoe, Eva; Kjaersgaard, Mimi; Zetterberg, Eva; Ostrowski, Sisse; Greinacher, Andreas; Rossing, Maria
Abstract: Heterozygous variants in the IKZF5 gene, encoding transcription factor Pegasus, were recently discovered to be causal of inherited thrombocytopenia (IT). We screened 90 patients suspected of inherited thrombocytopenia for variants in 101 genes associated with inherited bleeding disorders and report the clinical presentation of two Danish families with novel variants in IKZF5. Platelet ultrastructure and cytoskeleton were evaluated by immunofluorescent microscopy (IF) and found to be highly abnormal, demonstrating severe disturbances of distribution and expression of non-muscular myosin, filamin, β-tubulin and α tubulin. Number of alpha granules were reduced, and platelets elongated when evaluated by TEM. In both families a child carrying a rare IKZF5 variant was affected by developmental delay. The proband of family A presented with recurrent infections and was examined for an immunodeficiency. The concentration of naive B-cells was found moderately reduced by leucocyte subpopulation examination, indicating an impaired cellular immunity. T-cells were marginally low with reduced share and concentration of CD45RApos, CD31pos, CD4pos recent thymic immigrants as signs of reduced thymic output. The novel IKZF5 variants co-segregated with thrombocytopenia in both families and both probands had significant bleeding tendency. Through comprehensive characterizations of the platelet morphology and function linked to the specific phenotypes we add novel insight to IKZF5 -associated thrombocytopenia, which may help to identify and classify more cases with IKZF5 associated IT.